Difficulties Encountered by Student Teacher in Implementing Lesson Plan in the Practical Program at a Senior High School in Kudus - Faishol Khoir Syamsul Huda (Prominent, 2025)
The aim of this research is determine the difficulties that student teachers experiencing in the practicum programs at SMAN 2 Bae Kudus face and solution to overcome the difficulties in implementing RPP. Research instruments for this study include interviews, documentation, and audio-video materials. The method utilized in this research is qualitative, and it is conducted through case studies. For the aims of this study, data was collected from five students who were currently enrolled in the English Education Department at Muria Kudus University and were currently engaged in an internship program at SMAN 1 Bae Kudus in the academic year 2024/2025. Within the context of teaching, this study highlights ten difficulties that arise in three distinct phases: pre teaching, while teaching, and post teaching.  Students who are participating in the internship program at SMAN 1 Bae Kudus have the opportunity to implement lesson plans. There are five different strategies that may be utilized to solve the difficulties that they face. As a consequence of this, the researcher believes that the student teacher will be able to engage in self-reflection in order to assess difficultiesand adopt appropriate strategies in order to overcome difficulties that are encountered throughout the process of implementing the lesson plan in the an internship program. In order to prevent problems from occurring again and again, It is anticipated that the subsequent researchers will be able to overcome the difficulties associated with the implementation of lesson plans, which have not been discovered in this study. This will be accomplished by the utilization of alternative research approaches and the development of ways to mitigate these difficulties.